Enhancing athletic performance with complex contrast training: A Delphi study of elite strength and conditioning coaches - Luders, J.; Gleadhill, S.; Garrett, J.; Bennett, H. (International Journal of Sports Science & Coaching, 2024)
This Delphi study identifies how elite strength and conditioning coaches prescribe complex contrast training to team sport athletes. Thirty-eight elite strength and conditioning coaches with experience working in high performance settings participated in a three-round survey. Round one was used to collect open-ended responses regarding the programming of complex contrast training. Responses were formulated into statements for rounds two and three, where participants rated their level of agreement using a 9-point Likert scale (agreement threshold =80%). In round one, 139 statements were formulated. Twenty-seven statements reached consensus in round two, and four more in round three. Based upon consensus, complex contrast training is best used during the season and dedicated power blocks. It was recommended that strength and power exercises within complex contrast training pairings be performed for 3-4 sets of 3-4 repetitions. Loading of 85-90% of one repetition maximum (1RM) was recommended for strength exercises, with ~two repetitions in reserve, and BW-30% 1RM for power exercises, with three minutes of rest between contrast sets. Upper body pressing, upper body throwing, lower body squatting and hinging, and lower body jumping and bounding exercises were recommended. Coaches reported using complex contrast training to enhance power-focused training, and because it is more time efficient. Complex contrast training may be a time efficient method of improving athletic performance when training time is limited. Results from this study can guide the development of complex contrast training programs for team-sport athletes, and provides valuable insight into how elite coaches enhance performance.